Exploring different photocatalytic behaviors of CdxZn1−xSeyS1−y gradient-alloyed quantum dots via composition regulation. Issue 17 (29th July 2021) - Ying, Xiangjing; Liu, Yuxin; Liu, Zheng; Zhang, Menglong; Wang, Chuanglei; Wang, Weizhe; Gu, Huaimin; Huang, Runda; Luo, Dongxiang; Liu, Xiao
Abstract : Different photocatalytic behaviors of Cd x Zn1− x Se y S1− y gradient alloyed quantum dots via composition regulation. Abstract : Gradient-alloyed quantum dots (QDs) are new and interesting photocatalysts for efficient solar-to-chemical energy conversion to solve increasing energy and environmental problems. Nevertheless, few studies have been devoted to exploring structure–property relationships of gradient-alloyed QDs via the composition regulation. Herein we offer band-engineered gradient-alloyed QDs Cd x Zn1− x Se y S1− y prepared by stoichiometry control over the composition manipulation and has a funnel-shaped energy level. The effect of band structure on the photocatalytic performance of Cd x Zn1− x Se y S1− y QDs demonstrated that the regulation of light-harvesting range, charge carrier separation ability and redox reactivity can be achieved by composition and size adjustments. The results show that red QDs have the best electron/hole separation ability and widest photon capturing scope, while blue QDs possess the highest redox reactivity, realizing the contaminant degradation and CO2 reduction, simultaneously, with a high apparent rate constant k app of 0.4237 min −1 . Moreover, green QDs could be employed as a well-luminescent material owing to the fast electron–hole recombination rate. The mechanistic investigations reveal that different activities are dependent on a combination of two factors, that are ion migration-induced conversion of electron configuration and size-induced band bending. The understanding obtained in the present study is valuable for on-demand designing the unique properties of gradient-alloyed QDs.